The evolution of British immigrant integration policy after World War II: a historical and political science perspective - Kurcewicz, Urszula (Rocznik Integracji Europejskiej, 2014)
The paper presents the evolution of the British model of immigrant integration after World War II. It is a historical and political analysis. The author indicates the key elements of the British approach to decolonisation which were translated into concrete legal acts regulating the lives of the Commonwealth residents and immigrants arriving in the UK. The paper also discusses different dimensions of the integration of immigrants into British society. The analysis indicates that the multicultural model of immigrant integration adopted after World War II has been found to be dysfunctional, as British society has reached a state of super-diversity, becoming a very complex mosaic of races, religions and nationalities.